Performance Based Contracts in the Road Sector : Towards Improved Efficiency in the Management of Maintenance and Rehabilitation - Brazil's Experience - Lancelot, Eric (World Bank, Washington, DC, 2014)
This note aims at providing feedback on Brazil's successful experience in using performance based contracts in the rehabilitation and maintenance of the road networks. Since its introduction in the early 2000's, the use of this contract management model has progressively spread to reach, as of today, one third of the federal network and more than 10 percent of the states' networks, and expectations are for higher figures in the short run. The note highlights the context which led to the introduction of these contracts in the road sector and the strategic orientations adopted in their structuring. The model was notably expected to bring rationalization, accountability and credibility to the sector at a moment when road maintenance, though a crucial issue when considering the networks' characteristics and conditions, was not given sufficient consideration by the road administrations. The note then provides an evaluation of the positive achievements resulting from these contracts. The evaluation, comparing objectively performance based contracts to the traditional input-admeasurements approach, shows that these contracts brought an overall improved efficiency to the sector which translated to better road conditions at lower costs for the governments and reduced management burdens on the administrations. Finally, the note provides insights, gained from ten years of continuous learning, on the main lessons learnt, and perspectives on desirable evolutions in the future, while a balanced share of responsibilities and initiatives between the public and the private sectors is essential, strengthened administrations, fully accountable for preserving public interests, remain key to success; better articulating contract duration and rehabilitation works service life, which would lead to extended contract duration, is also one of the possible orientations for future performance-based contracts in Brazil.